Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10311-005-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute temperature dependency in the cleansing of tarry feathers utilizing magnetic particles

Abstract: We have conducted temperature-dependent studies on the removal of a solidified tarry residue from feathers using magnetic particles. These studies demonstrate an acute temperature dependency whereby no contaminant at all is removed below a certain temperature but, at and above this temperature, the removal rapidly approaches 100%. Significantly, this temperature is well below the temperature at which the tarry residue becomes a flowing liquid. This demonstrates that it is possible for magnetic cleansing to rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…The acute temperature dependency observed for the removal of tarry residue from duck and penguin feather clusters (Orbell et al 2005) is also observed for penguin plumage (Fig. 1 a).…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…The acute temperature dependency observed for the removal of tarry residue from duck and penguin feather clusters (Orbell et al 2005) is also observed for penguin plumage (Fig. 1 a).…”
Section: Resultssupporting
confidence: 51%
“…Thus, the effectiveness of iron powder as a dry cleansing agent for the removal of a wide range of contaminants from both feather clusters and from plumage has previously been demonstrated (Orbell et al 1999(Orbell et al , 2004. More recently, this technology has been shown to effectively remove tarry contamination from feather clusters, whereby a remarkable acute temperature dependency was observed (Orbell et al 2005). We have now extended this research to the removal of the same tarry contamination from the plumage of whole bird models where the same phenomenon occurs.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…These include: its use to remove contamination from oiled feathers (Orbell et al 2004;Dao et al 2006a), studies on the acute temperature dependence and thermodynamics of the pick-up process (Orbell et al 2005;Dao et al 2006b), the effect of pre-conditioners used in conjunction with iron powder for the removal of tarry and weathered oil (Dao et al 2006c;Orbell et al 2007) and its potential use to remove oil contamination from the surface of rock (Orbell et al 2007). …”
Section: Introductionmentioning
confidence: 99%